Human influenza vaccines and assessment of immunogenicity. (December 2010) - Zakay-Rones, Zichria
Influenza is responsible for the infection of approximately 20% of the population every season and for an annual death toll of approximately half a million people. The most effective means for controlling infection and thereby reducing morbidity and mortality is vaccination by injection with an inactivated vaccine, or by intranasal administration of a live-attenuated vaccine. Protection is not always optimal and there is a need for the development of new vaccines with improved efficacy and for the expansion of enrollment into vaccination programs. An overview of old and new vaccines is presented. Methods of monitoring immune responses such as hemagglutination-inhibition, ELISA and neutralization tests are evaluated for their accuracy in the assessment of current and new-generation vaccines.